(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study came under the title (The role of environmental media in promoting sustainable environment in Iraqi universities) to address sustainable environmental issues through environmental media, as this study is one of the descriptive survey studies. The study aimed to answer a number of questions that were formulated in light of the research problem to know the extent to which environmental media assumes its responsibility towards the public in finding solutions to environmental problems, and to reveal the extent of the target audience’s desire to interact with the topics raised by environmental media, as this study included three chapters as follows: Chapter One: The methodological framework and included (the research problem, the importance of the research, the research objectives, the type of research and its methodology, the research community and its sample, the research limits and areas, the research concepts and terms, previous studies), while the second chapter is the theoretical framework: which includes the nature and concept of environmental media and its determinants, in addition to the characteristics and standards of environmental media, the means, objectives and obstacles of environmental media, in addition to addressing the theory of collective responsibility, and finally the third chapter is the field study that included: the methodological research procedures, presentation and analysis of data, results and recommendations. The researcher reached a set of conclusions, the most important of which are: • Environmental media is clearly defined in the Iraqi media, as the respondents agreed to some extent at a rate of 40%, which calls for increasing environmental awareness in the Iraqi media. • Students in Iraqi universities have a clear perception regarding viewing the content of environmental media, and that the media is interested in environmental issues to some extent, as it obtained a rate of 38%. • The ineffectiveness of environmental media in Iraqi universities leads to the absence of social behavior in Iraqi universities, as it ranked first, I disagree, 43%..